The Effect of Smoking Dangers Education on Knowledge and Attitudes for Young Boys at SMPN 1 Long Pahangai - Bayau, Fransiska Haring; Kalsum , Umi; Rahman , Gajali (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of education on the dangers of smoking on knowledge and attitudes of adolescents. This type of research is quasy experimental. The population is young men at SMPN 1 Long Pahangai, totaling 63 people. The sampling technique is total sampling, so the sample is 63 people. Data analysis used the Wilcoxon test. The level of knowledge before being given education was mostly poor criteria (76.2%) and after being given education the criteria were good (100%). Attitudes about the dangers of smoking before being given education were mostly negative criteria (61.9%) and after being given education about the dangers of smoking all positive criteria (100%). There is an effect of education on the dangers of smoking on adolescent knowledge (p value 0.000 <α : 0.05) and there is an effect of education on the dangers of smoking on adolescent attitudes (p value 0.000 <α : 0.05). That means there is an influence of education on the dangers of smoking on the knowledge and attitudes of adolescents.